Scientific workshops with a dialogical approach: an effective tool for introducing science into vulnerable educational contexts - Guardiola-Fígols, Miquel; González, Aitor Gómez; Natividad-Sancho, Laura; Gairal-Casadó, Regina (Frontiers in Education, 2024)
The literature shows not only that science communication excludes the most vulnerable groups in society but also that it is of the utmost importance to make it more inclusive and available to all citizens.However, the inclusive communication experiences that are having some impact on society by including vulnerable groups have yet to cover all aspects of the issue. This article shows the positive results of the scientific workshops that take a dialogical approach from researchers from the Institute of Human Palaeoecology and Social Evolution (IPHES). The workshops on the "IPHES in the Local Area" program are designed to communicate science looking for scientific excellence at the highest level in urban centers that are of special complexity. The data were collected using pre-and post-test questionnaires given to 117 pupils from three primary schools where the science workshops were held.The data analysis shows that, after the workshops, participants had a greater interest in and appreciation of science.